Prebiotic formation of enantiomeric excess D-amino acids on natural pyrite - Ruiqi Li; Quanzheng Deng; Lu Han; Tianwei Ouyang; Shunai Che; Yuxi Fang (Nature Communications)
Abstract D-amino acids, found in excess in a minority of organisms and crucial for marine invertebrates, contrast with the more common L-amino acids in most life forms. The local prebiotic origin of D-amino acid enantiomeric excess in natural systems remains an unsolved conundrum. Herein, we demonstrate the formation of enantiomeric excess (ee) D-amino acids through photocatalytic reductive amination of α-keto acids on natural pyrite. Various amino acids with ee values in the range of 14.5–42.4%, are formed. The wavy arrangement of atoms on the surface of pyrite is speculated to lead to the preferential formation of D-amino acids. This work reveals the intrinsic asymmetric photocatalytic activity of pyrite, which could expand understandings on mechanism of asymmetric catalysis and chirality of inorganic crystals. Furthermore, it provides a plausible pathway for the prebiotic formation of D-amino acids, adding further evidence to the origin of D-amino acids enantiomeric excess in natural systems.